Measuring Party Strength: A New Systematic Framework Applied to the Case of German Parties, 1991–2013. Issue 1 (2nd January 2016) - Chiocchetti, Paolo
Abstract : An appropriate quantitative measurement of party strength is an essential precondition to any further qualitative assessment of partisan influence. The existing literature offers a number of individual indicators but fails to integrate them into a coherent systematic framework. This article fills that gap by proposing a new multi-dimensional and multi-level framework model to operationalise and measure party strength. The soundness of the approach is tested on the case of the evolution of German parties between 1991 and 2013.